The Pastoral Model of Educating Seniors at Universities of the Third Age at UPJPII in Krakow - Jan Dziedzic (Polonia Sacra)
Universities of the third age have become very popular in Poland and in the world. As institutions dealing with lifelong learning, they have the appropriate competencies to ensure that the various needs of seniors are met. U3A, established at UPJPII in Kraków in 2011, is one of such programs, dynamically operating in Poland. It is aimed not only at increasing the level of general knowledge but also at the religious formation of the students. The university has a religious profile and implements a pastoral and educational program, that includes lectures and workshops in the field of the Bible and anthropology, ethics, theology, philosophy and history of the Church, as well as an educational and cultural program (religious tourism, theatre arts), that is meant as a form of creative support for seniors. Plenary lectures and seminar workshops are complemented with the offer of additional educational and developmental classes. They include foreign language learning, computer courses, tourism, sports and cultural activities. Thanks to our U3A, many elderly people have improved their self-esteem and sense of dignity. They have also learned how to overcome problems related to old age and barriers preventing them from full participation in social and parish life.